2022
DOI: 10.1016/j.sleep.2021.07.009
|View full text |Cite
|
Sign up to set email alerts
|

A year in review: sleep dysfunction and psychological distress in healthcare workers during the COVID-19 pandemic

Abstract: The Covid-19 outbreak has taken a substantial toll on the mental and physical wellbeing of healthcare workers (HCWs), impacting healthcare systems at a global scale. One year into the pandemic, the need to establish the prevalence of sleep dysfunction and psychological distress in the face of COVID-19, identify risk and protective factors and explore effective countermeasures remains of critical importance. Despite implicit limitations relating to the quality of available studies, a plethora of evidence to-dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 98 publications
3
62
0
2
Order By: Relevance
“…In the majority of other COVID-19 studies, including our first survey in 2020 [ 12 ], nurses were shown to have worse depression compared to doctors [ 3 , 26 , 27 , 28 , 29 ]. Reasons cited have been that nurses have closer more frequent contact with patients and worked longer hours than usual [ 26 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of other COVID-19 studies, including our first survey in 2020 [ 12 ], nurses were shown to have worse depression compared to doctors [ 3 , 26 , 27 , 28 , 29 ]. Reasons cited have been that nurses have closer more frequent contact with patients and worked longer hours than usual [ 26 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of other COVID-19 studies, including our first survey in 2020 [ 12 ], nurses were shown to have worse depression compared to doctors [ 3 , 26 , 27 , 28 , 29 ]. Reasons cited have been that nurses have closer more frequent contact with patients and worked longer hours than usual [ 26 , 27 , 29 ]. Interestingly, our cohort of matched doctors had significantly worse depression in 2021 compared to 2020, and their overall depression score in 2021 became worse than our nursing staff’s.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 crisis has almost certainly placed a significant strain on health systems across the globe and has exposed health care workers to an unprecedented threat. 3,4 Not surprisingly, health care workers are not only placed at the core of the pandemic but are in a particularly vulnerable position. 4 They are predisposed to a number of risks: heavy workloads, unpredictable work patterns, and a higher risk of infection, which might have consequences on their health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Not surprisingly, health care workers are not only placed at the core of the pandemic but are in a particularly vulnerable position. 4 They are predisposed to a number of risks: heavy workloads, unpredictable work patterns, and a higher risk of infection, which might have consequences on their health and wellbeing. 5,6 Moreover, in comparison to the general population, health care workers are facing increased professional and personal responsibilities during the pandemic, which may lead to an additional psychological burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation